Code Variety Broadcasted by East Kalimantan Radio Stations - Sukron Marzuki; Djatmika Djatmika; Sri Marmanto (Hasanuddin University, 2019)
This research aimed at elaborating the variety of code-switching and code-mixing used in radio broadcast in East Kalimantan. This research used qualitative descriptive method and applied sociolinguistics study. In the analysis, the researcher employed Poplack and Muysken theory. Data sources were collected from radio broadcast in three radio stations representing three largest cities in East Kalimantan, such as Samarinda, Balikpapan, and Tenggarong. The type of data were conversation that appeared within the Pilihan Pendengar program from each of three stations: Gemaya 104.5 FM (Balikpapan), RB Radio 87.7 FM (Samarinda) and SBK 107.3 FM (Tenggarong). The research finds that there are varieties of code-switching, including: intra-sentential (40 data), inter-sentential (19 data) and extra-sentential (9 data). For code-mixing, this research finds three variants, which are alternation (24 data), insertion (14 data) and congruent lexicalization (8 data). The data are obtained from different languages, such as Indonesian, Javanese, Kutainese, English and Arabic.